Pre-Service Teachers' Metaphorical Perceptions Regarding the Concept of Curriculum - AKINOĞLU, ORHAN (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2017)
The purpose of this study was to reveal pre-service teachers' perceptions regarding the concept of 'curriculum' through metaphors. Phenomenology, which is one of the qualitative research designs, was used in the study. Data of the study was obtained by asking a total of 123 pre-service teachers, including 84 females and 39 males and studying at various departments in Ataturk Faculty of Education at Marmara University in Turkey in the spring semester of 2013-2014 academic year, to complete the statement Curriculum is like.... Because.... The collected data was analysed by content analysis technique and interpreted. According to the findings of the study, pre-service teachers produced a total number of 107 valid metaphors regarding the concept of 'curriculum', which were then categorized by considering their common features. Eight categories were obtained for the concept of 'curriculum'. In general, pre-service teachers were found to have positive perceptions regarding the concept of 'curriculum'.
Keywords: curriculum; curriculum perception; metaphor; teacher education; learning and teaching; phenomenology; EDUCATION; THINKING; BELIEFS